2002
DOI: 10.1046/j.1365-2036.2002.01243.x
|View full text |Cite
|
Sign up to set email alerts
|

Ranitidine, 75 mg, over‐the‐counter dose: pharmacokinetic and pharmacodynamic effects in children with symptoms of gastro‐oesophageal reflux

Abstract: SUMMARYBackground: The use of over-the-counter antacids has increased in children under the age of 12 years, and has been followed by an apparent increase in the use of over-the-counter histamine-2 receptor antagonists. However, the pharmacokinetic and pharmacodynamic effects of over-the-counter histamine-2 receptor antagonists in the paediatric population are largely unknown. Aim: To evaluate the pharmacokinetics and pharmacodynamics of a single dose of the over-the-counter histamine-2 receptor antagonist, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 22 publications
0
26
1
3
Order By: Relevance
“…Após a administração da droga, foi observado um aumento significativo do pH intragástrico por 5 a 6 horas, além de perfis farmacodinâmico e farmacociné-tico adequados. Assim, tal como em adultos, essa dose de ranitidina pode ser usada para controle de sintomas de queimação em crianças maiores 24 .…”
Section: A Criança Com Queimação Retroesternalunclassified
“…Após a administração da droga, foi observado um aumento significativo do pH intragástrico por 5 a 6 horas, além de perfis farmacodinâmico e farmacociné-tico adequados. Assim, tal como em adultos, essa dose de ranitidina pode ser usada para controle de sintomas de queimação em crianças maiores 24 .…”
Section: A Criança Com Queimação Retroesternalunclassified
“…This makes H 2 RAs well suited to "on-demand" use. Another plus for these drugs is that there are pediatric data supporting the use and safety of the H 2 RAs cimetidine, ranitidine, nizatidine, and famotidine in infants and children [27][28][29][30]. Cimetidine tends to be less frequently used in children, as it has more side effects than the others.…”
Section: H 2 Rasmentioning
confidence: 92%
“…21 In the multi-center study that represented Phase 1 of the current single-center study, using a single 75 mg oral dose produced a positive correlation between ranitidine concentration and gastric pH. 9 A substantial decrease in gastric acidity lasted over 5-6 hours.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacodynamic and pharmacokinetic results of this multi-center trial (Phase 1) of fixed dose ranitidine (OTC Zantac 75) in these 19 children were reported earlier. 9 Phase 2. As an add-on to the above study, the six subjects from our center who completed Phase 1 received ranitidine 5 mg/kg orally (maximum dose 150 mg) approximately 12 hours after the dose of OTC Zantac 75 or placebo, having consumed a regular meal in the interim.…”
Section: Designmentioning
confidence: 99%